Reproductive Control And Female Subordination In Batak Culture: A Muted Group Theory Analysis Of “Catatan Harian Menantu Sinting” - Aisyah Herlita Setyaningrum (FAKULTAS DAKWAH UIN SALATIGA, 2025)
This study aims to analyze the patriarchal system and the subordination of women within Batak culture as depicted in the film Catatan Harian Menantu Sinting. The research focuses on how cultural control over women’s bodies and reproductive expectations is reflected in the social structure and family relationships. A qualitative approach was used, employing Roland Barthes’ semiotic analysis to identify cultural symbols and myths that reinforce patriarchal norms. In addition, Muted Group Theory was applied to understand the silencing of women’s voices within the patriarchal system. The findings reveal that the film represents women’s subordination through reproductive pressure, where women are expected to bear male children to continue the family lineage. This norm not only restricts women's autonomy in making life choices but also reinforces gender inequality that disempowers women across social, cultural, and psychological dimensions. The study affirms that patriarchal culture in Batak society plays a significant role in perpetuating the subordination of women through reproductive control.